Achromatopsia: clinical features, molecular genetics, animal models and therapeutic options. (4th March 2018) - Hirji, Nashila; Aboshiha, Jonathan; Georgiou, Michalis; Bainbridge, James; Michaelides, Michel
ABSTRACT: Achromatopsia is an autosomal recessive condition, characterised by reduced visual acuity, impaired colour vision, photophobia and nystagmus. The symptoms can be profoundly disabling, and there is no cure currently available. However, the recent development of gene-based interventions may lead to improved outcomes in the future. This article aims to provide a comprehensive review of the clinical features of the condition, its genetic basis and the underlying pathogenesis. We also explore the insights derived from animal models, including the implications for gene supplementation approaches. Finally, we discuss current human gene therapy trials.